2000
DOI: 10.1051/analusis:2000169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secondary interactions on high performance size exclusion chromatography. Application to the fractionation of landfill leachates

Abstract: Many authors undertook the chemical characterisation of the leachates generated by the municipal landfills. The review of the data of the literature (see [1]) shows that several separative and analytical techniques were primarily used i.e. the ultrafiltration, the liquid-liquid extraction, the permeation chromatography on Sephadex gels, the adsorption on Amberlite XAD resins, and the gas chromatography. This led us to use a different method: the high performance size exclusion chromatography (HPSEC).We carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, our literature search illustrated in Table 1 showed that this was only done in a few of the references. Le Coupannec et al (36) also observed a slight alternation of the retention time in the chromatograms when using NaNO 3 and CH 3 COONH 4 as eluents for HPSEC. This could be due to the influence of the nature of the salt on the matrix pore and the compound size.…”
Section: Discussionmentioning
confidence: 91%
“…However, our literature search illustrated in Table 1 showed that this was only done in a few of the references. Le Coupannec et al (36) also observed a slight alternation of the retention time in the chromatograms when using NaNO 3 and CH 3 COONH 4 as eluents for HPSEC. This could be due to the influence of the nature of the salt on the matrix pore and the compound size.…”
Section: Discussionmentioning
confidence: 91%
“…In absence of secondary interactions, longer elution time corresponds to smaller MW. Secondary interactions, such as adsorption on the column material, hydrophobic and electrostatic effects, lead to advanced or delayed elution that violates the mechanism of purely steric exclusion (Le Coupannec et al, 2000). While hydrophobic effects are important at high ionic strength of eluent, M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 the role of electrostatic effects (particularly, ion exclusion) increases with decrease of eluent ionic strength (Specht and Frimmel, 2000). Eluents of low ionic strength (2-20 mM) provide high chromatographic resolution for anionic compounds, however, elution of cationic compounds is delayed due to the ion exclusion (Le Coupannec et al, 2000). Eluents with high ionic strength may be undesirable because "macromolecule aggregation in wastewater will be destroyed with the addition of Na + , which can substitute divalent metal ions (such as Ca 2+ ) involved in extracellular polymeric substances bridging" (Guo et al, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…2a. The effect can be explained with the influence of ionic interactions as the secondary separation mechanism [28,29].…”
Section: Sec Icp Ms Characteristic Of Iodine Compounds Extracted Frommentioning
confidence: 99%